Functional Patterns of Lexical Bundles and Limitations in Academic Writing by Thai L2 English Learners - Attapol Khamkhien (Journal of English Language Teaching and Linguistics, 2021)
Lexical bundles, which serve as markers of fluent and appropriate language use, are referred to as "building blocks of discourse" because they occur frequently in written texts and help readers and writers process information more quickly. They also provide important linguistic functions. However, lexical bundles can vary across genres, domains and even sections of the same work, which can be challenging for novice and non-native writers. The purposes of this study are to explore how Thai L2 undergraduate students use lexical bundles in their academic papers written in English and to compare the use of lexical bundles with that in two written corpora: the British Academic Written English (BAWE) and Cambridge Academic English (CAE). A total of 53 research reports, or approximately 615,750 words, from Thai L2 students of English language studies and applied linguistics were systematically compiled and analysed. The most frequent four-word n-grams in the corpora were then identified and their types and functions categorised. Keyword analysis was used to compare the key n-grams identified in each academic corpus. The results show that native and non-native writers use lexical bundles in rather different ways. Some patterns that did not occur in the reference corpus were overused by Thai L2 English students. The data suggest that the inclusion of phraseology in L2 writing instruction has pedagogical implications. This study can be of great pedagogical value, especially for EAP instructors, as it reveals frequent patterns in the form of a pedagogically useful list of word combinations. By extension, the data presented can be used by non-native writers or academics, especially novice Thai writers, to improve their use of phraseological patterns in writing academic research reports or writing for publication.